Whole-Genome Single-Nucleotide Polymorphism (SNP) Analysis Applied Directly to Stool for Genotyping Shiga Toxin-Producing Escherichia coli: an Advanced Molecular Detection Method for Foodborne Disease Surveillance and Outbreak Tracking - Singh, Navjot (J Clin Microbiol, 2019)
Whole-genome sequencing (WGS) of pathogens from pure culture provides unparalleled accuracy and comprehensive results at a cost that is advantageous compared with traditional diagnostic methods. Sequencing pathogens directly from a primary clinical specimen would help circumvent the need for culture and, in the process, substantially shorten the time to diagnosis and public health reporting. Unfortunately, this approach poses significant challenges because of the mixture of multiple sequences from a complex fecal biomass. The aim of this project was to develop a proof of concept protocol for the sequencing and genotyping of Shiga toxin-producing Escherichia coli (STEC) directly from stool specimens. We have developed an enrichment protocol that reliably achieves a substantially higher DNA yield belonging to E. coli, which provides adequate next-generation sequencing (NGS) data for downstream bioinformatics analysis. A custom bioinformatics pipeline was created to optimize and remove non-E. coli reads, assess the STEC versus commensal E. coli population in the samples, and build consensus sequences based on population allele frequency distributions. Side-by-side analysis of WGS from paired STEC isolates and matched primary stool specimens reveal that this method can reliably be implemented for many clinical specimens to directly genotype STEC and accurately identify clusters of disease outbreak when no STEC isolate is available for testing.